2016
DOI: 10.1136/tobaccocontrol-2015-052897
|View full text |Cite
|
Sign up to set email alerts
|

Public understanding of cigarette smoke constituents: three US surveys

Abstract: Introduction The Tobacco Control Act requires public disclosure of information about toxic constituents in cigarette smoke. To inform these efforts, we studied public understanding of cigarette smoke constituents. Methods We conducted phone surveys with national probability samples of adolescents (n=1125) and adults (n=5014) and an internet survey with a convenience sample of adults (n=4137), all in the USA. We assessed understanding of cigarette smoke constituents in general and of 24 specific constituents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 29 publications
7
69
0
Order By: Relevance
“…Cross-sectional studies in the US, UK, Australia, Mexico, and Canada using convenience and probability samples have found that the public was most aware that carbon monoxide (48–86%), nicotine (64–94%), and tar (48–86%) are in cigarette smoke (Borland & Hill, 1997; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996a, b, 2003a, b; Hammond et al, 2006; Ipsos-Eureka, 2009; Moracco et al, 2016; O'connor et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). Fewer people were aware that cyanide (13–72%) and arsenic (6–58%) are in cigarette smoke (Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b, 2003b; Hammond et al, 2006; Moracco et al, 2016; Siahpush et al, 2006; Wiseman et al, 2016), and very few people knew that other constituents such as nitrosamines (6–25%), polonium (8–24%), and mercury (11–26%) are in cigarette smoke (Boynton et al, 2016; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b; Siahpush et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). One study of pregnant women in Lebanon found that 70% knew cigarette smoke contained addictive substances and carcinogens (Chaaya et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cross-sectional studies in the US, UK, Australia, Mexico, and Canada using convenience and probability samples have found that the public was most aware that carbon monoxide (48–86%), nicotine (64–94%), and tar (48–86%) are in cigarette smoke (Borland & Hill, 1997; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996a, b, 2003a, b; Hammond et al, 2006; Ipsos-Eureka, 2009; Moracco et al, 2016; O'connor et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). Fewer people were aware that cyanide (13–72%) and arsenic (6–58%) are in cigarette smoke (Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b, 2003b; Hammond et al, 2006; Moracco et al, 2016; Siahpush et al, 2006; Wiseman et al, 2016), and very few people knew that other constituents such as nitrosamines (6–25%), polonium (8–24%), and mercury (11–26%) are in cigarette smoke (Boynton et al, 2016; Brewer et al, 2016; Cummings et al, 2004b; Environics Research Group, 1996b; Siahpush et al, 2006; Swayampakala et al, 2015; Wiseman et al, 2016). One study of pregnant women in Lebanon found that 70% knew cigarette smoke contained addictive substances and carcinogens (Chaaya et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…One study of pregnant women in Lebanon found that 70% knew cigarette smoke contained addictive substances and carcinogens (Chaaya et al, 2004). One study of a U.S. national probability sample assessed awareness of 24 cigarette smoke constituents, randomly assigning respondents to answer about a panel of four constituents (Boynton et al, 2016; Brewer et al, 2016). More than a third of participants were unaware of all of the constituents in their panel, and only 8% knew at least three of the four constituents they were asked about.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From September 2014 to May 2015, we recruited a probability sample of 5014 U.S. adults, including 1164 smokers (Boynton et al, 2016; Brewer et al, 2016). Our paper focuses on an experiment conducted with established cigarette smokers (defined as those who reported smoking “some days” or “every day” and who had smoked at least 100 cigarettes in their lifetime).…”
Section: Methodsmentioning
confidence: 99%